Rhythm as the structural basis of a phonographic production (Revista Argentina de Musicología, 2022)
This article is based on an exploratory work on the use of rhythm machines for phonographic production from the late 1970s onwards. Starting from the hypothesis that thanks to the ease of manipulation offered by the Roland TR-808 for the creation of infinite rhythmic bases, it has become the preferred creative tool of music producers who continue to work with it to this day. Belonging to a heterogeneous music scene in constant transformation worldwide, the Roland TR-808 rhythm machine imposes itself with its accessible features, giving rise to a sound poetics based on the idea of futuristic sound that remains to this day.In the first place, I propose to account for some of the operational potentialities that Roland brand rhythm machines have added over time to the point of becoming, in some cases, the only instrument in phonographic productions. Second, to explain the innovative importance of these instruments in some popular genres of the period of the late 1970s and early 1980s. Finally, the rise of hip hop as a consequence of the use of the TR-808, in addition to the genres and compositions derived from experimentation with the instrument.
Keywords: rhythm machines; Roland; TR-808; hip hop